PENGARUH LATIHAN CONE DRILL OUTSIDE INSIDE TERHADAP PENINGKATAN KEMAMPUAN DRIBBLING DI AL HIJAZ FUTSAL ACADEMY - Edmonda Ignacia, Yustinus; Pramono, Made (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cone drill outside inside practice can improve dribbling skills in futsal players. Low dribbling ability can affect the quality of players in possession of the ball during matches. The purpose of this study is to prove the effect of cone drill outside inside on improving dribbling skills in U-17 futsal players at Al Hijaz Academy. This research is in a quantitative descriptive design. The subject of this study involved 25 players. The data collection technique in this study is with observation and test techtechniques. The test used, namely the dribbling pretest, was then given cone drill outside inside, after which a posttest dribbling was carried out. The data analysis technique used was a paired sample t-test with a sig (2-tailed) value of 0.000 < 0.05 which means that there is a significant influence of the cone drill inside outside exercise on the improvement of dribbling ability in futsal players at Al Hijaz Academy.